Contributions of PPL2 dopaminergic neurons to olfactory representations in Drosophila melanogaster - Marquand, Katie May (Trinity College Dublin. School of Medicine. Discipline of Physiology, 2026)
Animal responses to the same stimulus vary with experience, motivation, hunger, age, and other internal or external conditions. This raises the question of how the brain encodes stimulus identity while allowing flexible behavioural outputs. In this thesis, we use the species Drosophila melanogaster to investigate how dopamine modulates internal olfactory representations. Drosophila is an ideal model for studying olfactory coding due to its well-mapped circuitry, small neuron number, and capacity for complex behaviour. Although anatomically distinct from vertebrate brains, flies share conserved neuromodulators and functional organisation. Here, we focus on sparse olfactory representations in Kenyon Cells (KCs), whose processes form the Mushroom Body (MB), a centre for olfactory learning and memory. This work examines the PPL2 dopaminergic neuron cluster which innervates the MB calyx, the entry point for olfactory inputs, positioning it to modulate odour representations upstream of memory formation. Connectome analysis reveals KCs and the inhibitory neuron APL as the main postsynaptic targets of PPL2. Synapse location analysis suggests that PPL2 forms a presynaptic component of microglomeruli in the calyx, indicating a modulatory role within these complex synaptic structures. Additionally, calcium imaging experiments with dopamine receptor knockdown suggest that dopamine acts via Dop2R to differentially modulate KC subsets. Preliminary evidence indicates that KC responses vary with hunger state, potentially mediated by dopamine. Finally, a naïve olfactory behavioural assay shows that PPL2 activation enhances responses to odour regardless of valence. Overall, these findings support a role for PPL2 dopaminergic input in shaping olfactory processing by modulating distinct KC populations. We identify key circuit elements for future study and provide initial evidence for how PPL2 activity influences both neural representation and behaviour.
APPROVED
Keywords: Sensory perception; Olfaction; Dopamine; Circuits; Drosophila